2017
DOI: 10.1158/1078-0432.ccr-17-0023
|View full text |Cite
|
Sign up to set email alerts
|

miR-196b-5p Regulates Colorectal Cancer Cell Migration and Metastases through Interaction with HOXB7 and GALNT5

Abstract: miR-196b-5p has been previously implicated in malignant transformation; however, its role in colorectal cancer has not been fully explored. In this study, we examine the clinical and biological relevance of miR-196b-5p, and the molecular pathways regulated by miR-196b-5p in colorectal cancer. miR-196b-5p expression was quantitated by qRT-PCR in 2 independent cohorts composed of 292 patients with colorectal cancer in total, to explore its biomarker potential. Transient and stable gain- and loss-of-function expe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
52
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 40 publications
5
52
0
Order By: Relevance
“…Recent studies in colorectal cancer demonstrated that miR-196b-5p expression promotes migration and growth of metastases (41). Therefore, to determine the biological outcome of miR-196b-5p overexpression in human gastric cancer, we investigated the influences of miR-196b-5p in gastric cancer cell proliferation and invasion.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies in colorectal cancer demonstrated that miR-196b-5p expression promotes migration and growth of metastases (41). Therefore, to determine the biological outcome of miR-196b-5p overexpression in human gastric cancer, we investigated the influences of miR-196b-5p in gastric cancer cell proliferation and invasion.…”
Section: Resultsmentioning
confidence: 99%
“…miR-196b-5p overexpression has been reported in gastrointestinal cancer types, such as pancreatic (47), colorectal (41), and gastric (48). However, the molecular relationship between miR-196b-5p and HOXA10 is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty-four studies demonstrated the downregulation of twenty-five miRs associated with advanced TNM stage: miR-302c 67 , miR-466 68 , miR-340 69 , miR-196b-5p 70 , miR-944 71 , miR-30d 72 , miR-22 50 , miR-296 73 , miR-384 74 , miR-199b 48 , miR-128 75 , miR-33b 76 , miR-155-5p 77 , miR-154 78 , miR-149 79 , miR-194 80 , miR-133b 37 , miR-15a 34 , miR-100 81 , miR-133a 41 , miR-335 82 , miR-378a-3p 58 , miR-378a-5p 58 , miR-218 83 and miR-16 34 . Two studies demonstrated the upregulation of miR-182 43, 44 associated with advanced TNM stage and others 22 studies pointed 23 different upregulated miRs associated with advanced TNM stage.…”
Section: Resultsmentioning
confidence: 99%
“…Among the evaluated studies, 49 demonstrated the downregulation of miR-199b 47, 48 , miR-6852 106 , miR-302c 67 , miR-466 68 , miR-650 123 , miR-196b-5p 70 , miR-944 71 , miR-30d 72 , miR-296 73 , miR-187 124 , let-7a-5p 98 , miR-132 99 , miR-206 100 , miR-148a 125 , miR-33b 76 , miR-99b-5p 120 , miR-154 78 , miR-217 126 , miR-149 79 , miR-194 80 , miR-7 56 , miR-24-3p 54 , miR-29b 127 , miR-15a 34 , miR-16 34, 36 , miR-204-5p 128 , miR-96-5p 121 , miR-193a-5p 108 , miR-100 81 , miR-133a 41 , miR-139-5p 129 , miR-124-5p 130 , miR-335 82 , miR-378 101 , miR-126 40 , miR-378a-3p 58 , miR-378a-5p 58 , miR-218 83 , miR-138 110 , miR-625 111 , miR-212 112 , miR-124 131 , miR-22 49 , miR-133b 39 , miR-193a-3p 104 , miR-195 113 and miR-30c 103 associated with worse prognosis (lower overall survival) of CRC patients. Fifty-six studies identified the upregulation of miR-181a 3133 , miR-182 43, 44 , miR-1296 84 , miR-888 64 , miR-28-5p 132 , miR-183 45, 46 , miR-200c 114 , miR-34a 133 , miR-15a-5p 134 , miR-181c 135 , miR-24-3p 53 , miR-16 35 , miR-7 55 , miR-96 86 , miR-1260b 115 , miR-20a-5p 63 , miR-517a 87 , miR-503 136 , miR-106b 88 , miR-211 137 , miR-320e 89 , miR-592 90 , miR-196a 57 , miR-196b 57 , miR-376a …”
Section: Resultsmentioning
confidence: 99%
“…Buprenorphine exposure was associated with significant downregulation of miR-196a and miR-196b. Multiple predicted and/or validated target genes of miR-196a and miR-196b have been associated with developmental disorders (ZMYND11 72 for autism 73,74 and intellectual disability 75 ; HOXB7 76 for Huntington's disease 77 and neural tube defects 78,79 ). Other targets of downregulated miRs in opioid cases also have a role in opioid addiction (AQP4, 80,81 NR2C2 82 ) and co-dependence of alcohol and nicotine (NR2C2 83 ).…”
Section: Moud Associated With Altered Fce Protein Cargo: Pilot Analmentioning
confidence: 99%